The Banggai Cardinalfish : Natural History, Conservation, and Culture of Pterapogon kauderni. - Vagelli, Alejandro A. (John Wiley & Sons, 2011)
The Banggai cardinalfish, Pterapogon kauderni, is a fascinating species that possesses a series of remarkable biological characteristics making it unique among coral reef fishes. It has been the focus of studies in reproduction, ecology, population genetics and evolution. In addition, since its rediscovery in the late 1990s, it has become tremendously popular in the international ornamental fish trade, and indiscriminate collecting has led to its inclusion in the 2007 IUCN Red List as an endangered species. This book is divided into three main parts: a general introduction to the fish, includin.